Linking reforestation policies with land use change in northern Vietnam: why local factors matter - Clement, Floriane; Amezaga, Jaime M. (2008)
In many countries worldwide, similar state policies on land management have been implemented as a response to deforestation in mountainous areas. So far, few studies have examined to which extent these policies have actually contributed to reforestation. This is the focus of our analysis, based on a case study in Vietnam. Because land access and land use were traditionally governed by common rules, we examine land use changes from an institutional perspective. We use the Institutional Analysis and Development IAD) framework, coupled with an historical perspective and the analysis of actors' perception and dominant narratives on land management and forests. Results show that national policies significantly interfered with local factors, leading to a complex course of decision-making and action. Substantial reforestation in the area was not a response by farmers to policy incentives but rather the unexpected outcome of the disruption of local institutions by these policies. We argue that, because national interventions have relied on false or exaggerated narratives and beliefs, their implementation is in conflict with the local reality in upland areas, leading to unpredictable and locally dependent outcomes. We defend hence the need for local level studies and also recommend considering local institutions for land use change analysis in contexts where land use systems are characterised by a high degree of human interaction.